Pengaruh Green Packaging Terhadap Green Perceived Value dan Green Perceived Risk Serta Dampaknya Pada Green Purchase Intention - Muhammad Rizki Fayad; Hairudinor (JURNAL BISNIS DAN PEMBANGUNAN, 2024)
Abstract: This research aims to test and determine the influence of green packaging on green perceived value and green perceived risk, as well to test and determine the influence of green perceived value and green perceived risk on green purchase intention. The research location was chosen at Starbucks in Banjarmasin City. A total of 100 respondents were determined and selected using accidental sampling. Questionnaries were used to collect data and PLS-SEM was used to test the hypotheses. The results show that green packaging has a significant positive effect on green perceived value and a significant negative effect on green perceived risk, also the green perceived value has a significant positive effect on green purchase intention, while green perceived risk has a significant negative effect on green purchase intention   Keywords: Green Packaging, Green perceived Value, Green Perceived Risk, Green Purchase Intention